Childhood urolithiasis in Britain. Issue 4 (April 1973) - Ghazali, S.; Barratt, T. M.; Williams, D. I.
Abstract : 120 children with urinary calculi were treated between 1966 and 1971. 75% were male, and the median age of diagnosis was 3 years. In 34 there were associated urological abnormalities and in 8 a metabolic cause of calculi was identified. 12 of 67 children had hypercalciuria. In 95 children the urine was infected on admission to hospital; in 76, particularly the younger children, this was with Proteus species. Calculi recurred after surgery in 13 children, and in 9 the only identifiable factor was failure to eradicate the Proteus infection.